EFEKTIVITAS METODE SAS (STRUKTURAL ANALITIK SINTETIK) DALAM MENINGKATKAN KEMAMPUAN MENULIS PERMULAAN SISWA KELAS 1 SDN REJOSARI 02 PADA PEMBELAJARAN BAHASA INDONESIA : Penelitian Kuantitatif One Group Pretest Posttest - Ady gunawan; Duwi Nuvitalia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the low early writing ability of first-grade students at SDN Rejosari 02 Semarang City, particularly in arranging syllables into complete sentences. The low writing ability was caused by the use of less effective and monotonous learning methods, which made students less interested in writing activities. To address this problem, the Structural Analytic Synthetic (SAS) method was applied, which is in line with linguistic principles that decompose sentences into words, syllables, and letters. The purpose of this research was to determine the effectiveness of the SAS method in improving students’ early writing skills. This study used a quantitative approach with a one-group pretest–posttest design. The research subjects were all 28 first-grade students. Data were collected through tests (pretest and posttest), observation, and documentation. The results of the Wilcoxon Signed Rank Test showed that the significance value was 0.05 with Zhitung (4.62) > Ztabel (1.96), indicating that H1 was accepted. This means that there was a significant effect of applying the SAS method on students’ early writing skills. The N-gain score obtained an average of 0.81, categorized as very effective. Students’ learning outcomes increased significantly, with the average pretest score of 37.5 rising to 88.04 on the posttest, and learning mastery improved from 0% to 100%. Therefore, the SAS method is effective in enhancing students’ early writing skills.